Analisis Kompetensi Pedagogik Guru Dalam Perencanaan Bahan Pembelajaran Kelas 6 SD Inpres Antang 1 - Safitri, Nurmaningsih; Sabillah, Bellona Mardhatillah; Citra, Aukiya (Educatio, 2023)
This study aims to find out how the pedagogic competence of teachers class in planning learning materials for grade 6 students at UPT SPF SD Inpres Antang 1. Class teachers and school authorities have an important role ibn planning or preparing learning materials for use in learning as a medium so that the material being taught is conveyed properly as stated in the Regulation of the Minister of education and culture number 62 0f 2013 concerning National Education Standards which explained about the lesson plan designed in the form of a syllabus and RPP which refers to the Content Standards. Learning planning includes preparation of learning implementation plans and preparation of media, resources of study, learning assesment tools, and learning scenarios. This study is a descriptive qualitative research with data collection techniques namely observation, interview, and decomentation. Informants in this study are the principal, 3 homeroom teachers for grade 6, and 1 subject teachers. Result research shows the preparation of Class 6 teachers in preparing materials learning. Supporting factors that influence the material planning learning namely the creativity and skills of teachers, cooperation of teachers, students and parents, learning components, as well as facilities and infrastructure adequate.